Loss of RIP3 alleviates insulin resistance and inflammation in gestational diabetes mellitus mice via TLR4/MyD88/NF-κB signaling pathway - He, Yingying; Zhu, Weiwei; Qiu, Yuebo; Zhou, Kening (BMC pregnancy and childbirth, 2025)
Gestational diabetes mellitus (GDM) is diabetes with reduced glucose tolerance that is found or diagnosed during pregnancy, which seriously affects the health of mothers and infants, and its incidence is increasing year by year. The necroptotic apoptosis regulator RIP3 has been proposed to be active in managing pancreatic islet cell survival and inflammatory response. Still, its role and mechanism in GDM have not yet been clarified. The effect of high glucose induction and RIP3 on the viability of Pancreatic β-cells and insulin secretion was observed in vitro experiments. C57BL/6J mice were used to establish the GDM model. Weight, serum glucose levels, and insulin levels were measured to evaluate the improvement of diabetes symptoms in GDM mice by sh-RIP3. The levels of IL-1β, IL-6, and TNF-α were determined by ELISA and qRT-PCR assays. Hematoxylin and Eosin (HE) staining assay was applied to detect islet cell morphology and inflammatory damage in pancreatic tissue. Progeny weight and litter size were also recorded to evaluate reproductive function in GDM mice. Western blot was performed to express TLR4/MyD88/NF-κB signal-related proteins. Knockdown of RIP3 ameliorated GDM symptoms, improved glucose tolerance and insulin sensitivity, suppressed inflammation, and enhanced fetal outcomes, possibly by TLR4/MyD88/NF-κB signaling pathway activation in GDM mice. The present study provided evidence that the downregulation of RIP3 alleviates insulin resistance and inflammation in GDM mice by mediating the TLR4/MyD88/NF-κB signaling pathway, which made RIP3 a new potential therapeutic target for GDM treatment in the future.